OBJECTIVES OF FINANCIAL POLICY OF THE RUSSIAN FEDERATION IN THE MEDIUM TERM - A. G. Siluanov (Финансы: теория и практика, 2017)
The paper analyzes the mid-term goals of the Russian Finance Ministry. The implementation of the goals should ensure the transition of the economy to an equilibrium state with a stable and predictable macroeconomic environment. One of the tools to accomplish the goals is budgetary rules; therefore, the paper sets forth the requirements and describes modern approaches to their transformation. The role of information technologies in improvement of the tax collection and other payments to the budgetary system is considered in the context of key task characteristics in the field of budget revenues administration. To enhance the budget performance, it is necessary to integrate the budgeting and the procurement processes, expand the scope of the treasury support of government contracts and develop the state financial control system. The paper defines the functioning conditions of the financial system as a mechanism for transformation of savings into investments